Mental health services in Nicaragua: Lessons for South Africa - Shefer, Tammy (PINS-Psychology in Society, 2025)
This paper arises out of research into an alternative mental health system - the Nicaraguan model. It aims to highlight aspects of the latter which we suggest are useful guidelines within the construction of appropriate, accessible and enlightened mental health services in South Africa, and hopes to build on a recent commentary on Nicaragua presented by Vogelman (1988c). It should be noted that the author has no personal experience with the Nicaraguan situation and that this paper relies on secondary sources.